واقع تطبيق أبعاد المنظمة المتعلمة في جامعة تشرين دراسة مسحية على كلية الاقتصاد الثانية (Latakia University Journal - Economic and Legal Sciences Series, 2017)
تواجه المنظمات العديد من التحديات التي تتطلب منها اتباع أساليب إدارية حديثة ومرنة لتتمكن من التكيف والتأقلم مع بيئتها، وجاءت المنظمة المتعلمة مفهوماً إدارياً حديثاً يقوم على التفاعل والمرونة وحرية التفكير لابتكار نماذج وطرق جديدة من شأنها التكيف مع التغيرات المحيطة. هدف هذا البحث إلى التعرف على مفهوم المنظمة المتعلمة فهو مفهوم حديث العهد، والتعرف على واقع تطبيق أبعاد المنظمة المتعلمة في كلية الاقتصاد الثانية في جامعة تشرين، حيث قامت الباحثة باعتماد استبيان Marsick&Watkins لأبعاد المنظمة المتعلمة، وتم توزيع الاستبيان على العينة الممثلة بموظفي كلية الاقتصاد الثانية على اختلاف مستوياتهم الإدارية. توصلت الدراسة إلى اعتبار كلية الاقتصاد الثانية منظمة متعلمة بمستوى متوسط وفقاً لمقياس ليكرت الخماسي.Organizations face many challenges that require them to follow a modern and flexible management methods, to be able to adjust and adapt to their environment learning organization concept is based on modern administrative interaction, flexibility and freedom to think, to create models and new ways that will adapt to the surrounding changes.The objective of this research is to identify the concept of the learning organization, which is a recent concept, and recognize the reality of the application of the learning organization dimensions at the faculty of the second economy, Tishreen University.where the researcher adoption Marsick & Watkins questionnaire to the dimensions of the learning organization was the questionnaire distributed to the representative sample the staff of the Faculty of the second economy on different administrative levels , The study concluded that the Faculty of the second economics is learning organization at average rate according to the average Likert scale Quintet.